California Advocate's Drum Major for Justice Dinner Honoring Julian Bond - Watkins, Howard::::::::: (1987)
Les Kimber, Julian Bond holding his award and shaking hands with Pauline Kimber, Mark Kimber Julian Bond and Pauline Kimber looking at camera